Perbandingan Tingkat Kebugaran Jasmani Peserta Didik yang Mengikuti Ekstrakurikuler Bolavoli di SMA Negeri 2 Lamongan dan SMA Negeri 3 Lamongan - Muhammad Nizam Wildan Abror; Taufiq Hidayat (Departement of Mathematics Education, 2024)
Physical fitness is one of the needs that must be met so that many activities such as playing, working, exercising and studying do not feel excessively tired. The goal is to influence the human body's ability to develop its tasks better and develop the body's strength and abilities. Extracurricular sports are various activities carried out outside class hours and carried out outdoors. The aim is to support students' achievements in the sports they like. This research aims to determine the comparison of the physical fitness levels of students who take part in extracurricular volleyball at SMAN 2 Lamongan and SMAN 3 Lamongan. Researchers use a comparative type in this research with a quantitative approach. The total population for this study was 60, divided into 30 in each agency. The instrument used is MFT. Sample collection used purposive sampling. The results of this research are that there is no significant difference between the physical fitness of students who take part in volleyball extracurriculars at SMAN 2 Lamongan and SMAN 3 Lamongan as seen based on the t-count value (-0.022 < 1.671) and Sig value (0.983 > 0.05).